Pathways to Reconciliation: the Kitcisakik Land-Based Education Initiative. Issue 3 (3rd July 2019) - Arellano, Alexandra; Friis, Joseph; Stuart, Stephen A.
ABSTRACT: Grounded in settler colonialism and resurgence, this paper presents multiple accounts gleaned from students who underwent experiential ways of learning about Indigenous cultures and sociopolitical issues through a land-based education experience considered as a contribution to building reconciliation. For over 8 years, the semi-nomadic community of Kitcisakik in Western Québec has received non-Indigenous students to experience living 'off the land' and share Anicinape ways. Originally inspired by a community desire to share and transmit Anicinape culture while re-appropriating wider territories of their 'occupied' ancestral land, this became a grassroots social economy initiative, offering 4- to 10- day educational trips for students. In addition to encouraging cultural dialogue and mutual respect, the initiative exemplifies the benefits of Indigenous learning pedagogies that are both experiential and land-based. Students describe how they physically and spiritually encounter Indigenous resilience via a confrontation of the neocolonial intricacies evident in contemporary Canada. Such critical self-reflection is necessary in Canada's nascent era of decolonization.